2014
DOI: 10.1007/s10753-014-9953-7
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Ameliorates Cisplatin-Induced Nephrotoxicity by Inhibiting Renal Inflammation in an Experimental Model

Abstract: Cisplatin is a platinum-based chemotherapy drug. However, its chemotherapeutic use is restricted by serious side effects, especially nephrotoxicity. Inflammatory mechanisms have a significant role in the pathogenesis of cisplatin-induced nephrotoxicity. Thalidomide is an immunomodulatory and anti-inflammatory agent and is used for the treatment of various inflammatory diseases. The purpose of this study was to investigate the potential nephroprotective effect of thalidomide in a mouse model of cisplatin-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 26 publications
4
26
1
1
Order By: Relevance
“…It has been shown that neutrophil 60 infiltration into the gastric mucosa has a critical role in the devel- suppress the production of TNF-a, IL-1b, IL-6 and NO in gastroin-89 testinal tissue [13][14][15][16]. In addition, our previous studies have also 90 confirmed that thalidomide exerts its anti-inflammatory effects by 91 suppressing the production of proinflammatory cytokines [17][18][19]. 92 TNF-a has a major role in the pathophysiology of ethanol-induced 93 gastric mucosal inflammation and damage [7,9,20].…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…It has been shown that neutrophil 60 infiltration into the gastric mucosa has a critical role in the devel- suppress the production of TNF-a, IL-1b, IL-6 and NO in gastroin-89 testinal tissue [13][14][15][16]. In addition, our previous studies have also 90 confirmed that thalidomide exerts its anti-inflammatory effects by 91 suppressing the production of proinflammatory cytokines [17][18][19]. 92 TNF-a has a major role in the pathophysiology of ethanol-induced 93 gastric mucosal inflammation and damage [7,9,20].…”
mentioning
confidence: 75%
“…190 2.9. Determination of malondialdehyde (MDA) levels 191The gastric tissue content of MDA was measured according to192 the thiobarbituric acid (TBA) method[19]. Briefly, 100 ll of the 193 supernatant was added to a reaction mixture containing 100 ll 194 of 20% (w/v) trichloroacetic acid (TCA) and 200 ll of…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental animal studies, focused on the role of antioxidants such as vitamin E, vitamin C, erythropoietin, thalidomide, melatonin, alpha lipoic acid, and fish oil, found out that these antioxidant agents are effective in cisplatin toxicities 15,31 .…”
Section: Comprehensive Neurologic and Neurophysiologic Examinationsmentioning
confidence: 99%
“…Significant elevation of myeloperoxidase (MPO) level in cisplatin nephrotoxicity has been observed along with pro-inflammatory cytokines; TNF-α, and IL-1β indicative of provoked inflammatory response as reported earlier (Amirshahrokhi and Khalili, 2015). Myeloperoxidase (MPO) was found to exert a primary role in chronic inflammation (Podrez et al, 2000) as well as in oxidative damage in various body organs (Vita et al, 2004) and demonstrates an essential mechanistic link between oxidation and inflammation (Madhusudhana Rao et al, 2011).…”
Section: Discussionmentioning
confidence: 73%